Penerapan Model Problem Based Learning Terhadap Hasil Belajar Mahasiswa Jurusan Akuntansi - Ginting, Wenny Anggeresia; Pangemanan, Shane Anneke; Amalia, Reski; Purba, Ficky Marchfirmanto (Universitas Gorontalo, 2023)
This research aims to investigate the implementation of the Problem Based Learning (PBL) model among accounting students at Politeknik Negeri Manado. The study employs a non-equivalent design, comparing an experimental class using the PBL model to a control class without the PBL model. The results of the research indicate that there is a significant influence of the Problem Based Learning (PBL) model on the learning outcomes of accounting students at Politeknik Negeri Manado. Furthermore, based on the n-gain score, the learning outcomes of the experimental class fall into the effective category, signifying that the implementation of PBL is effective in enhancing learning outcomes in the subject of financial accounting, specifically in the cash flow material.